Implementation of advanced characterisation techniques for assessment of grinding effects on the surface integrity of WC–Co cemented carbides. (15th March 2018) - Yang, J.; Roa, J. J.; Schwind, M.; Odén, M.; Johansson-Jõesaar, M.P.; Esteve, J.; Llanes, L.
ABSTRACT: Grinding is a key step on the manufacturing process of WC–Co cemented carbides (hardmetals). In this work, an investigation of grinding effects on the surface integrity of hardmetals is conducted. It is done by combining diverse advanced characterisation techniques: X-ray diffraction, field emission-scanning electron microscopy, electron back scatter diffraction, focused ion beam – 3D tomography and transmission electron microscopy. The study is carried out in a fine-grained WC–Co grade. Besides ground state, polished surface finish condition is assessed for comparison purposes. It is evidenced that grinding induces significant alterations: 3D tomography illustrates microcracking exists down to 2.5 μm depth with a highly anisotropic distribution at the subsurface, large compressive residual stresses extending until subsurface levels of about 12 μm, and phase transformation of binder from the original fcc phase into the hcp one, as well as severe plastic deformation observed within the binder at the surface level. Invited keynote papers from EuroPM2017, Milan.